Working group report: Astroparticle and neutrino physics - Gandhi, R; Mohanty, S; Souradeep, T; Agarwalla, S; Bhattacharya, K; Brahmachari, B; Crittenden, R; Goswami, S; Ghoshal, P; Lindner, M; Mani, H; Mitra, S; et al. (2006)
The working group on astroparticle and neutrino physics at WHEPP-9 covered a wide range of topics. The main topics were neutrino physics at INO, neutrino astronomy and recent constraints on dark energy coming from cosmological observations of large scale structure and CMB anisotropy. © Indian Academy of Sciences.